Creative Arts-Based Therapies for Stroke Survivors: A Qualitative Systematic Review - Lo, Temmy Lee Ting; Lee, Janet Lok Chun; Ho, Rainbow Tin Hung (Frontiers in Psychology, 2019)
Background: Stroke is a life-threating cerebrovascular disease. Without proper and immediate treatment, it can cause long-term disabilities and even death. While current rehabilitation focuses on functional needs, it does not fully address the psychosocial issues. Creative arts-based therapies, however, may have the potential to be of assistance. Method: A systematic review was conducted to synthesize the qualitative findings of the stroke survivors’ positive and negative experiences in participating in creative arts-based therapies. A systematic literature search was conducted across diverse databases. A thematic synthesis was adopted to analyze the results from different qualitative studies and mixed methods studies. Results: Among the 367 studies extracted from various databases, 11 studies met the inclusion criteria and were of acceptable quality. The following five analytical themes were identified: functional restoration, psychological support, social engagement, spiritual experience, and short-comings and barriers. Conclusion: Creative arts-based therapies demonstrated their strengths in addressing psychosocial needs for stroke survivors. Different art modalities are perceived to be useful in achieving different therapeutic goals. Therapies based on a single art modality or combined modalities have different specialties and characteristics. Further research is needed to demonstrate the differential benefits or special advantages of using single or multiple art modalities as well as having qualified therapists in creative arts-based therapies.